RELIGIOUS INTERPRETATION ON PANCASILA METHODOLOGICALLY AND EMPIRICALLY IN IMPLEMENTING ISLAMIC INSIGHT IN INDONESIAN ARCHIPELAGO - Wahyudin Wahyudin (Akademika : Jurnal Pemikiran Islam, 2019)
Religious interpretations of Pancasila in implementing Islamic insights result from interpretations of religious teachings. For example, the interpretation of the principles of Indonesian unity is the Islamic ummah. The Indonesian context of the unity of all nations in the archipelago is a unity; Indonesian people with BhinekaTunggalIka ties. Indonesia is a great nation since the Kingdom of Srivijaya, Majapahit with Palapa pledge is strong, strong and advanced and respected by other countries. The kingdom collapsed not because of an external threat, but it was damaged from the inside. The Indonesian nation at present is a great nation, in essence feared by foreign countries. Indonesia cannot be bombarded from the outside. The method of infiltration into various ways; liberalism, secularism, 'radicalism, fundamentalism and so on. This country is prosperous, “gemah ripah loh jinawi” should be toto tentrem kerto raharjo. The source of his wealth is the struggle of foreign countries no matter how and how. Our present and future duties are to defend the sovereignty of the Republic of Indonesia in any way. The fact is that government policies tend to side with foreigners. If you are not vigilant early on, the Indonesian nation can be lost. For example, in Singapore, Malay tribes were destroyed, American Indians were marginalized, Australia aboriginal tribes were isolated, Palestinians had no territory. Jakarta Betawi tribes began to be evicted. Keywords: Interpretation, Islam, Pancasila and implementation